Favorable therapeutic response of osteoporosis patients to treatment with intravenous zoledronate compared with oral alendronate - Al-Bogami, Mohammed M. (Saudi Med J, 2015)
OBJECTIVES: To evaluate the efficacy of orally-administered alendronate compared with intravenously-administered zoledronate. METHODS: This prospective study was carried out at Barts Health HNS Trust between April 2010 and March 2012. This study compares changes in bone mineral density (BMD) in 234 patients treated with 2 bisphosphonates: alendronate taken orally, and zoledronate administered intravenously. One hundred and eighteen patients received alendronate at 70 mg/week, while 116 patients received zoledronate once annually. Dual energy x-ray absorptiometry was used to measure BMD of the left hip and anterior-posterior spine (lumbar L1-L4) skeletal sites at baseline, and at one-, and 2-years post-treatment. RESULTS: This study provides evidence that lumbar spine BMD increased by 3.6% in patients receiving alendronate, and 5.7% in patients receiving zoledronate after 2 years compared with baseline values (p=0.0001 for both). Total hip BMD decreased in patients treated with alendronate by 0.4% but increased in patients receiving zoledronate by 0.8% (p=0.0001). CONCLUSION: This study provides evidence that zoledronate is more effective than alendronate in treating patients with osteoporosis and with no gastrointestinal (GI) serious side effects. Furthermore, zoledronate appears to have the added advantage of a better safety profile in patients suffering from GI intolerance of oral bisphosphonates.